2010
DOI: 10.1074/jbc.m109.082776
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Assembly of Pilus Subunits of Streptococcus pneumoniae

Abstract: Pili are surface-exposed virulence factors involved in bacterial adhesion to host cells. The Streptococcus pneumoniae pilus is composed of three structural proteins, RrgA, RrgB, and RrgC and three transpeptidase enzymes, sortases SrtC-1, SrtC-2, and SrtC-3. To gain insights into the mechanism of pilus formation we have exploited biochemical approaches using recombinant proteins expressed in Escherichia coli. Using site-directed mutagenesis, mass spectrometry, limited proteolysis, and thermal stability measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 31 publications
6
45
0
Order By: Relevance
“…All the members of this family of putative pilin subunits have LPXTG-type cell wall sorting sequences that are presumably targeted by sortases (15). Sortase-mediated isopeptide bond cross-linking stabilizes and strengthens Gram-positive bacterial pili (18,20) and may mediate bacterial adhesion to host cells (1,8,34). In this regard, it is possible that the nine putative pilin isopeptide linkage domains of BapA1 may facilitate the assembly of BapA1 into a pilus-like structure on the bacterial surface.…”
Section: Discussionmentioning
confidence: 99%
“…All the members of this family of putative pilin subunits have LPXTG-type cell wall sorting sequences that are presumably targeted by sortases (15). Sortase-mediated isopeptide bond cross-linking stabilizes and strengthens Gram-positive bacterial pili (18,20) and may mediate bacterial adhesion to host cells (1,8,34). In this regard, it is possible that the nine putative pilin isopeptide linkage domains of BapA1 may facilitate the assembly of BapA1 into a pilus-like structure on the bacterial surface.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Subsequently isopeptides were identified in proteins known to form, or associated with, pili. [4][5][6][7][8] All bacterial isopeptides are found β-sheet domains resembling the CnaA or CnaB folds protein Cna from Staphylococcus aureus. [9,10] CnaA and CnaB domains are predicted to occur in thousands of bacterial surface proteins, and isopeptide bonds emerge as a very common posttranslational modification underpinning Gram-positive pilus formation and stability.…”
mentioning
confidence: 99%
“…Notably, in both domains, the isopeptide bonds connect the first and last ␤-strand in the ␤-barrel (which are located side-by-side due to the unusual IgG fold described above), in analogous fashion to a belt buckle, indicating that in RrgC these bonds assist in the stability of the core ␤-barrel. It is of note that these bonds had been previously shown to confer thermal stability and resistance to proteolysis to RrgC (22). This arrangement is distinct from that seen for RrgA, where isopeptide bonds stabilize the different halves of a ␤-sandwich (26).…”
Section: Resultsmentioning
confidence: 85%
“…In RrgC, the isopeptide bonds of domains D2 and D3 had been identified through sequence comparisons and mutagenesis studies; the latter indicated that both bonds play a key role in protein stability (22). Notably, in both RrgB and RrgC, the stabilization of the fold by intramolecular isopeptide bonds plays a significant role in the efficient recognition of the pilin subunits by their cognate sortases (22) underlining the key role played by these bonds for stability of the architecture of the entire pilus. Thus, the structuring of pilus-forming proteins as "beads on a string," with each domain stabilized by a covalent isopeptide bond, is a common signature in extracellular Gram-positive fibers.…”
Section: Discussionmentioning
confidence: 99%